A retrospective study of isatuximab-pomalidomide-dexamethasone in relapsed/refractory systemic AL amyloidosis - Sargam Rachit Vohra; Sriram Ravichandran; Darren Foard; Ana Martinez-Naharro; Lucia Venneri; Marianna Fontana; Carol J. Whelan; Philip N. Hawkins; Julian Gillmore; Helen J. Lachmann; Shameem Mahmood; Ashutosh D. Wechalekar (Haematologica)
Not available.